Studi Komparasi Kurikulum Sekolah Dasar di Indonesia dan Jepang - Ronald Felix Yanuar (Jurnal Dharma PGSD, 2021)
This research is a qualitative literature study with a comparative method. This research has a background on technological and human developments in Indonesia which continue to change with the times so that appropriate steps are needed to be able to implement and develop curriculum in the future. By looking at Japan implementing and designing curriculum in classroom learning, it is hoped that it can be an illustration for policy and curriculum formulation in Indonesia. This study draws data from various literary sources such as journals, articles, books, and official publications related to the curriculum from Indonesia and Japan. Bereday's comparative research model is used to present and analyze the research data. The validity of the data was tested by triangulation of sources by analyzing various literature sources. The results of this study indicate the similarities contained in the thematic learning values ​​and competencies contained in the curriculum in Indonesia and Japan. In education in Japan, it is seen that the application of moral education is very thick in learning activities in the classroom. This can be an illustration for curriculum development in Indonesia